Lactobacillus fermentum UCO-979C beneficially modulates the innate immune response triggered by Helicobacter pylori infection in vitro - Garcia Castillo, V. (2018)
Helicobacter pylori infection is associated with important gastric pathologies. An aggressive proinflammatory immune response is generated in the gastric tissue infected with H. pylori, resulting in gastritis and a series of morphological changes that increase the susceptibility to cancer development. Probiotics could present an alternative solution to prevent or decrease H. pylori infection. Among them, the use of immunomodulatory lactic acid bacteria represents a promising option to reduce the severity of chronic inflammatory-mediated tissue damage and to improve protective immunity against H. pylori. We previously isolated Lactobacillus fermentum UCO-979C from human gastric tissue and demonstrated its capacity to reduce adhesion of H. pylori to human gastric epithelial cells (AGS cells). In this work, the ability of L. fermentum UCO-979C to modulate immune response in AGS cells and PMA phorbol 12-myristate 13-acetate (PMA)-differentiated THP-1 (human monocytic leukaemia) macrophages in response to H. pylori infection was evaluated. We demonstrated that the UCO-979C strain is able to differentially modulate the cytokine response of gastric epithelial cells and macrophages after H. pylori infection. Of note, L. fermentum UCO-979C was able to significantly reduce the production of inflammatory cytokines and chemokines in AGS and THP-1 cells as well as increase the levels of immunoregulatory cytokines, indicating a remarkable anti-inflammatory effect. These findings strongly support the probiotic potential of L. fermentum UCO-979C and provide evidence of its beneficial effects against the inflammatory damage induced by H. pylori infection. Although our findings should be proven in appropriate experiments in vivo, in both H. pylori infection animal models and human trials, the results of the present work provide a scientific rationale for the use of L. fermentum UCO-979C to prevent or reduce H. pylori-induced gastric inflammation in humans.